Ocean Charting - Watson, W. F. (The International Hydrographic Review, 2015)
The recent significant improvement in ocean charting is discussed and a comparison is made between the recently completed 5th Edition of the General Bathymetric Chart of the Oceans (GEBCO) and the new series of Small-scale International Charts. The recording of ocean bathymetric data is referred to with special reference to the GEBCO Plotting Sheet System and the increasing importance of digital methods for the recording and storage of these data. Despite their recent improvement, ocean charts are, for the most part, still based on sparse and inadequate data : there are probably many ocean dangers and shoals still to be found and charted, and most of those currently charted are based on old and sketchy reports that could well be erroneous or considerably in error. There is therefore a need for chart users to be aware of these déficiences in ocean charting, and for uniform procedures and standards to be adopted for the investigation and charting of ocean dangers and shoals. The need for the continued maintenance and improvement of ocean charts is emphasised, and the role of remote sensing from satellite observations as an aid to the detection of new bathymetric features in the ocean is referred to.